Development of E-dialysis Database Management System (DBMS) for computer-based documentation and mobile application with RFID technology / Nor Elysha Kamaruzaman and Ismarani Ismail - Kamaruzaman, Nor Elysha; Ismail, Ismarani (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
This paper outlined the development of E-dialysis Database Management System (DBMS) for electronic-based documentation, which is applied to computer device and mobile application, integrated with RFID technology. Digital transformation of data is critical as it offers a better approach in documenting and storing the crucial medical records. Issues related to human error such as losing or misplacing the documents could be prevented and these records are more protected. The general system encompasses local and cloud databases, a computer Graphical User Interface (GUI) and a mobile application for normal dialysis patients. The system also includes 13.56MHz High Frequency (HF) RFID technology which is inferred as an effective life-saving solution for the smallest percent of the unfortunate dialysis patients who have disabilities or in the End Stage Renal Disease (ESRD). In a way, they can communicate with their doctors or caregivers just by simply providing their RFID tagsthat contain their medical records. Not only that, RFID technology was used for the purposes of patient identification and medical data tracking. The tags are scanned on RFID reader which is linked to the Database Management System (DBMS) that are developed with MYSQL. A PC Graphical User Interface (GUI), created with Visual Basic, and a mobile application using AppSheet act as the monitoring tools of this proposed research. A dialysis monitoring system integrated with Database Management System (DBMS) using RFID technology has been successfully developed to help and provide increased security and convenience for the users.